Simulink Model in the Matlab System for Determining the Causes of Possible Damages of Cable Lines - O H. Kuldashov; T. Dadajonov; M.G. Tillaboyev (Genius Journals, 2023)
In this paper, a Simulink model is proposed in the MatLab system to determine the causes of possible damage to cable lines. The causes of possible damage to cable lines are analyzed, namely mechanical damage, damage during installation, damage due to soil settlement, damage associated with defects in the manufacture of the cable, aging of the insulation and other reasons. A model of a power cable is presented in the form of a chain diagram, consisting of five links. The obtained simulation results (change in the nature of the time dependences of input voltages and currents in the absence and presence of defects in the insulation), analysis of the results allows you to determine the absence or presence of a local defect in the cable insulation.
Keywords: cable lines; Simulink model; MatLab system; strength